GENDING RARE: ITS POTENTIAL AS A CHARACTER EDUCATION MEDIA BASED ON LOCAL AUTHORITY IN DENPASAR CITY - Hariswari, Kadek Paramitha; triyanto, Triyanto; Iswidayanti, Sri (Catharsis, 2019)
In the midst of technological advances, changes in mindset, behavior and habits of the people of Denpasar City did not cause Gending Rare to experience extinction even though its existence was not as before. Gending rare has the potential as a media for character education that can be analyzed in terms of the form and value contained therein. The method used in this research is qualitative method. Data collection techniques using observation, interview and document study techniques. The data validity technique uses source triangulation. Data analysis techniques using song form theory and character value theory. The results of this study found that the barrel used in Gending Rare is the pelog barrel and selendro barrel, with a slow, moderate, gangsar (deft), and fast tempo. The time bar or the time signature used is time bars 2/4 and time bars 4/4. The language used is Fine Balinese Language and Casual Balinese Language. The character values ​​contained are religious, honest, tolerance, discipline, hard work, creative, independent, curiosity, love of the motherland, communicative, caring for the environment, and responsibility. This research can broaden the perspective of readers about the existence of Gending Rare and provide information about the form and value of the characters contained in Gending Rare. Keywords : Gending Rare, Form, and Value of Character Education.